Potential of Ligand Conjugated Metallic Nanoparticles in the Treatment of Carcinoma in the Delivery of Plant-Derived Payload - Sarwa, Khomendra Kumar (Asian Journal of Pharmaceutics (AJP), 2024)
To attain the required therapeutic concentration of the drug at the target site with minimal exposure to normal cells, a targeted strategy is essential in cancer treatment. Because of its various advantages, a ligand-tagged bioactive medication is the ideal option. The use of natural therapeutic substances payload in the metallic nanoparticles conjugated with ligands is highlighted in the review. The most intriguing delivery system for these naturally occurring oncological medications is a nanoparticle-based drug delivery system because of its selectivity and specificity. Making a nanoparticle with metals enhances these benefits because of the synergistic profile in potential applications.